Stressful experiences impact clinical symptoms in people with endometriosis - Demetriou, L; Becker, CM; Martínez-Burgo, B; Invitti, AL; Kvaskoff, M; Shah, R; Evans, E; Lunde, CE; Cox, E; Garbutt, K; Zondervan, KT; Fox, E; et al. (BioScientifica, 2022)
Endometriosis is a chronic condition that affects ~10% of women globally. Its symptoms include chronic pelvic pain, heavy periods and tiredness/fatigue, which have been associated with poorer quality of life and mental health. We aim to explore the impact of the COVID-19 pandemic on pain and fatigue symptoms and their interactions with the impact on mental health in people with endometriosis. This global cross-sectional online survey study collected data from 4717 adults with self-reported surgical/radiological diagnosis of endometriosis between May and June 2020. The survey included questions on the current status and changes of endometriosis symptoms (pelvic pain, tiredness/fatigue, and bleeding patterns), mental health, pain catastrophising, and the impact of the COVID-19 pandemic on the respondents’ lives. Compared to 6 months earlier, Respondents reported a marked worsening of their endometriosis symptoms (endometriosis-associated pain (39.3%; 95% CI: 37.7, 40.5), tiredness/fatigue (49.9%; 95% CI: 48.4, 51.2) and bleeding patterns (39.6%; 95% CI: 38.2, 41)) and mental health (38.6%; 95% CI: 37.2, 39.9). Those with a pre-existing mental health diagnosis (38.8%) were more likely to report their symptoms worsening. Worsening of pain and tiredness/fatigue was significantly correlated with worsening of mental health (P < 0.001). The relationship between changes in mental health and (a) change in pain and (b) change in fatigue was found to be weakly mediated by pain catastrophising scores (pain: B = 0.071, lower limit of confidence interval (LLCI) = 0.060, upper limit of confidence interval (ULCI) = 0.082, tiredness/fatigue: B = 0.050, LLCI = 0.040, ULCI = 0.060). This study demonstrates that stressful experiences impact the physical and mental health of people with endometriosis. The findings highlight the need to consider psychological approaches in the holistic management of people with endometriosis.